Energy evolution of sandstone under different cyclic loading and unloading modes in true triaxial mode - ZHANG Qihang; MENG Xiangrui; ZHAO Guangming (矿业科学学报)
To clarify the impact of different cyclic loading and unloading modes on the energy evolution of sandstone, triaxial cyclic loading and unloading tests were conducted using the self-developed TAWZ-5000/3000 rock true triaxial testing system along different paths. By analyzing the stress-strain curves, the mechanical characteristics of sandstone were evaluated, revealing a linear functional relationship between the elastic energy density, dissipated energy density, and input energy density of the sandstone. The results indicate that: (1) Under different cyclic loading and unloading modes, the hysteresis loops exhibited distinct evolutionary characteristics with an increase in the maximum principal strain; under the same mode, increasing the number of cycles did not change the trend of hysteresis loop variation. (2) The failure strength and peak-to-valley strain of rock samples under different paths showed significant path dependence. The peak strength was lowest in the equal-amplitude cyclic loading and unloading mode, followed by the graded cyclic loading and unloading mode, with the stepped cyclic loading and unloading mode showing the highest peak strength. (3) In the equal-amplitude cyclic loading and unloading mode, the energy density of rock samples was greater, with the input energy density and dissipated energy density in the direction of major principal stress rapidly declining and then stabilizing, while the elastic energy density remained constant; under the other two modes, the input energy density, elastic energy density, and dissipated energy density in the direction of major principal stress exhibited a positive correlation growth trend with an increase in the number of cycles. The energy density in the directions of minor and intermediate principal stresses was significantly lower than that in the direction of major principal stress.